Applied Approach to Finance Education to Salesmen in Malambo, Atlantico - GOMEZ PEDROZA Fredy Julián; GONZALEZ SILVERA Stephane (Communications of International Proceedings, 2025)
This study addresses the financial management limitations faced by independent merchants in the municipality of Malambo, Atlántico, who operate under conditions of low financial literacy, high informality, and limited access to formal financial services. These constraints negatively affect the sustainability of their businesses and restrict local economic development. Although existing literature acknowledges the relevance of financial education for the stability and growth of microenterprises, a significant gap remains regarding applied, context-based educational models tailored to populations with low schooling levels and vulnerable socioeconomic environments, particularly in regions such as the Colombian Caribbean. To fill this gap, the study develops the Applied Financial Education Model PEDAF – Practical Finance for Growth through a qualitative and projective methodological approach. The process incorporated a documentary review, an exploratory diagnosis with local merchants, analysis of national and international best practices, and expert validation. The model is structured into four modules: income and expense recording, budget planning, responsible credit management, and savings habits, supported by practical templates, facilitator guides, and didactic materials adapted to the target population. Findings indicate that PEDAF is a relevant, applicable, and context-sensitive educational solution capable of strengthening financial planning, reducing reliance on informal credit, promoting business formalization, and enhancing the economic resilience of small merchants. The model is also projected as a scalable and replicable tool that contributes to financial inclusion and sustainable development goals in similarly vulnerable communities across Latin America.
Keywords: Applied model; Financial education; Independent merchants; Financial literacy; Financial inclusion; Microenterprise.